ANALISIS KONSISTENSI PERENCANAAN DAN PENGANGGARAN DAERAH - Burin, Ferdinandus Diri (Faculty of Economics and Business, University of Muhammadiyah Malang, 2015)
This study aims to: (1) to analyze the level of consistency of planning and budgeting document which occurred in the Lembata district Year 2012-2015; (2) look at the factors that cause inconsistencies; and (3) to formu-late policy priorities. To answer the purpose, this study used a descriptive evaluative methods, which are categorized as qualitative stream. The in-formants include the executive, legislative, and NGOs. Based on an anal-ysis tool Matrix Consolidated Planning and Budgeting, Analysis of Root Cause Analysis, and Analytical Hierarchy Process (AHP), the results showed that the documents of the most inconsistent is RPJMD-RKPD, while programs that have a risk of inconsistency so high is infrastructure development.Keywords : Budgeting , Inconsistency, Planning.